EFFECTS OF IL-6/IL-2 FUSION GENE TRANSFECTION ON TUMOUR CELL BIOLOGICAL CHARACTERISTICS IN VITRO AND IN VIVO - Yu, Xiaodan; Tang, Peixian; Zhao, Chunhua; Zhang, Mingwei; Peng, Shanyun; Liu, Yuanlin; Mao, Ning (Chinese Journal of Cancer Research, 2013)
In order to examine the feasibility of cytokine fusion gene transfer into tumor cells, a retroviral vector(pLXSN) for human interleukin 6/interleukin 2(IL6/IL2) fusion gene was constructed by using PCR and iigating the two genes with a synthesized oligonucleotides linker. The IL6/IL2 fused gene was introduced into B16 melanoma cell line mediated by retrovirus and the changes of adhesive and metastatic ability of fused genemodified cells were detected. The B16-IL6/IL2 cells showed efficient expression of both cytokines and decreased binding affinity with extracellular matrix ( laminin and Matrigel), accompanying with decreased metastases potentials. These data suggest that the mechanism involving the decreased metastases may relate with the changes of biological characteristics and immune stimulating activity of gene-modified ceils.